Development of automatic spam detection application based on modular programming - Subhan, S; Arifudin, R; Efrilianda, D A; Prasetiyo, B (Journal of physics. Conference series, 2021)
This article discusses developing an application for automatic spam detection based on modular programming. In general website development, certain development features cannot be used on other similar websites. We use modular programming to solve this problem. The problem is how to develop an automatic spam detection application based on modular programming. We used the software prototyping method for application development. The results of this study are obtained an automatic spam detection website application based on modular programming.